PENINGKATAN MOTIVASI DAN KEAKTIFAN BELAJAR IPAS MELALUI MODEL PBL BERBASIS TEKNOLOGI - Tata Agnesa Salsabila; Savitri Suryandari; Mahyuni Rahayu (JIP: Jurnal Ilmu Pendidikan, 2025)
This research aimed to enhance students motivation and learning engagement in IPAS (Natural and Social Sciences) for fifth-grade students at SDN Pakis 1 Surabaya. The study was prompted by the observed low levels of student motivation and engagement in IPAS learning. To address this, the Problem-Based Learning (PBL) model was implemented, integrating technology in the form of videos and the ZEP game. This classroom action research utilized both qualitative and quantitative approaches, with fifth-grade students from SDN Pakis 1 Surabaya serving as subjects. Data were collected through classroom observations, interviews, and learning engagement questionnaires. The findings indicate a significant increase in student motivation and learning engagement after the integration of the PBL model with videos and the ZEP game. Improved student motivation was evidenced by their enthusiasm and active participation in group discussions and problem-solving. Enhanced learning engagement was also observed through students' initiative in asking questions, expressing opinions, and actively participating in learning activities. This suggests that combining the PBL model with technology integration can be an effective strategy for creating more engaging and meaningful IPAS learning experiences